Nursing care of the first neonatal patient with Veno-arterial ECMO plus venting in Peru. - Alvarado-Soto, Gianina (2020)
We report the nursing care of the first newborn patient in Peru who used central veno-arterial (VA) extracorporeal membrane oxygenation (ECMO) - plus left atrial decompression cannula (VENT). We standardized specialized nursing care by identifying 15 diagnoses according to taxonomy II nursing diagnoses (NANDA) and 3 that could be incorporated into it for newborn care in ECMO.